Time of Disease‐Modifying Antirheumatic Drug Start in Juvenile Idiopathic Arthritis and the Likelihood of a Drug‐Free Remission in Young Adulthood. Issue 4 (28th March 2019) - Minden, Kirsten; Horneff, Gerd; Niewerth, Martina; Seipelt, Eva; Aringer, Martin; Aries, Peer; Foeldvari, Ivan; Haas, Johannes‐Peter; Klein, Ariane; Tatsis, Stefanie; Tenbrock, Klaus; Zink, Angela; et al.
Abstract : Objective: To study juvenile idiopathic arthritis (JIA) long‐term outcomes in relation to the time of initiation of biologic disease‐modifying antirheumatic drug (bDMARD). Methods: Outcomes of JIA patients prospectively followed by the Biologika in der Kinderrheumatologie (BiKeR) and Juvenile Arthritis Methotrexate/Biologics Long‐Term Observation (JuMBO) registers were analyzed with regard to drug‐free remission and inactive disease, functional status and quality of life, and surgery. To analyze the influence of early bDMARD therapy on outcomes, patients were assigned to 3 groups based on the time from symptom onset to bDMARD start (G1: ≤2 years, G2: >2 to ≤5 years, and G3: >5 years). Propensity score–adjusted outcome differences were analyzed by multinomial logistic regression analyses among the groups. Results: A total of 701 JIA patients were observed for mean ± SD 9.1 ± 3.7 years. At the last follow‐up (disease duration mean ± SD 14.3 ± 6.1 years), 11.7% of patients were in drug‐free remission, and 40.0% had inactive disease. More than half of the patients reported no functional limitation, while 5% had undergone arthroplasty, and 3% had eye surgery. At the 10‐year time point, patients in G1 (n = 108) were significantly more likely to be in drug‐free remission than those patients who began treatment later (G2, n = 199; G3, n = 259), with 18.5%, 10.1%, and 4.9%, respectively. Patients in G1 had significantly lower disease activity (clinical Juvenile Arthritis Disease Activity Score in 10 joints = 4.9), a better overall well‐being (18.2% patient global assessment score = 0), and higher functional status (59.2% Health Assessment Questionnaire score = 0), compared to patients in G3 (7.1, 8.4%, and 43.7%, respectively). G1 patients required arthroplasty significantly less frequently than G3 patients and had significantly lower disease activity over time than patients in both G2 and G3. Conclusion: Early DMARD treatment is associated with better disease control and outcomes, which supports the concept of a "window of opportunity" for JIA.